Supply Chain Management Performance of HIV/AIDS Commodities and Factors Affecting It at Health Facilities of SNNPRS of Ethiopia; from the Perspective of Achieving 90-90-90 Strategies - Damtie TA; Ibrahim AJ; Yikna BB (Dove Medical Press, 2020)
Teklewold Abiye Damtie, 1 Awol Jemal Ibrahim, 2 Berhan Begashaw Yikna 3 1Department of Pharmacy, Arba Minch College of Health Science, Arba Minch, Ethiopia; 2School of Pharmacy, Faculty of Health Science, Jimma University, Jimma, Ethiopia; 3Department of Pharmacology, School of Pharmacy, College of Medicine, Debre Berhan University, Debre Berhan, EthiopiaCorrespondence: Berhan Begashaw Yikna Email berhan.uog1912@gmail.comBackground: Health facilities (HFs) need an extensive range of antiretroviral (ARV) drugs and related HIV/AIDS commodities for diagnosis, prevention, and treatment of HIV/AIDS. This study was aimed to assess supply chain management performance from the perspective of achieving 90-90-90 treatment strategy at HFs of Southern Nations, Nationalities and People’s Regional State (SNNPRS), Ethiopia.Methods: Facilities based cross sectional study design in 30 HFs (9 hospitals and 21 health centers) and five pharmaceuticals fund and supply agencies (PFSAs) was conducted. The HFs were selected randomly. Semi-structured questionnaires and observation checklists with logistic indicators assessment tools (LIATs) were used to collect data for HIV/AIDS related services from November 2016 to May 2017. In addition, we used in-depth face to face interview and thematic approach. Quantitative data were entered into Epi-Data version 3.1 and transported to SPSS version 20 to analyze the result. Qualitative data were analyzed using thematic approach.Results: Only 9 (30%) HFs had received their orders from PFSA on time from date of report. Average lead time for ARV drugs was 46.4 days in hospitals and 59.2 days in health centers (HCs). Sixteen (60.7%) HFs reported their completed report and requisition format (RRF). From this, 53.3% HFs order was refilled correctly in quantity from that they need. Inventory accuracy rate was 77%. Major HFs, 20 (66.7%) faced at least one-time emergency order for ARV drugs, HIV test kits and viral load (VL) supplies. Whereas, 9 (30%) hospitals and 5 (16.67%) HCs were out of stock two and three times respectively. Sixteen (53.3%) commodities stocked out at least once in six months. Nevirapine (NVP) 10 mg/5 mL in 240 mL was the most stocked out (13 times) for an average 22 days. Uni gold was stocked out (16 times) with average of 34.5 days. Wastage rate was 2.5%. Twenty-five (83.3%) facilities had good storage conditions (> 80% to the standard).Conclusion: Unsatisfactory data records, stock-outs, interrupted reports, inaccurate inventory and wastage rates were indicators for defective supply chain management of HIV/AIDS commodities. Respective organizations should improve their responsible activities to secure commodities availability.Keywords: HIV/AIDS, supply chain management, Ethiopia